2019
DOI: 10.3390/f10100895
|View full text |Cite
|
Sign up to set email alerts
|

Topography Affects Tree Species Distribution and Biomass Variation in a Warm Temperate, Secondary Forest

Abstract: A thorough understanding of carbon storage patterns in forest ecosystems is crucial for forest management to slow the rate of climate change. Here, we explored fine-scale biomass spatial patterns in a secondary warm temperate deciduous broad-leaved forest in north China. A 20-ha plot was established and classified by topographic features into ridge, valley, gentle slope, and steep slope habitats. Total tree biomass varied from 103.8 Mg/ha on the gentle slope habitats to 117.4 Mg/ha on the ridge habitats, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The low dominance in the RGF must be related to the high slope found at the site. Very steep areas do not support very large trees due to the instability of the terrain (Gonçalves et al, 2018;Wang et al, 2019). In these areas of greater slope, the substrate develops on shallow soil.…”
Section: Discussionmentioning
confidence: 99%
“…The low dominance in the RGF must be related to the high slope found at the site. Very steep areas do not support very large trees due to the instability of the terrain (Gonçalves et al, 2018;Wang et al, 2019). In these areas of greater slope, the substrate develops on shallow soil.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted in the built-up area of Beijing, China (40 • 00 N, 116 • 20 E). The study area located in the northeast of the Huabei Plain in north China is characterized by warm temperate deciduous broad-leaved forests [28]. Beijing has a temperate, humid, monsoonal continental climate characterized by hot and rainy summers, cold and dry winters, and short spring and autumn seasons [6].…”
Section: Study Sitesmentioning
confidence: 99%
“…The effect of topography on vegetation carbon density in Jiangxi province is works in the following two ways: (1) It affects soil properties by restricting water and heat conditions [62], which in turn affect species composition, forest structure and function, and ultimately lead to differences in forest vegetation carbon density [14,63]. Correlation analysis showed that there were extreme or significant correlations between terrain factors (altitude and slope) and forest structure factors, which indirectly proved the effect mechanism of topography on FVCD for Jiangxi province (Table 12).…”
Section: Effects Of Topography On Vegetation Carbon Densitymentioning
confidence: 99%